Nutritional Status, Development Level, and Psychosocial Function of Preschool Children - Adawiyah, Asyifa Robiatul; Azijah, Izattul (JHE (Journal of Health Education), 2020)
Background: Childhood is a critical period of growth and development. Children with malnutrition will cause a decrease in nutritional status so that children become malnourished, it affects physical growth disorders, the quality of intelligence, and future development. Methods: This type of research that used in this study was an observational study with a cross-sectional design, The sample of this study were all students of the play group and Kindergarten in Mutiara 17 August Bekasi, totaling 59 children. Results: there was a significant relationship between the history of exclusive breastfeeding and the incidence of stunting in Mutiara 17 August Bekasi (p <0.05), there was a significant relationship (p <0.05) between education, employment and foster care of a mother with functions children’s development using the DENVER II instrument. Speech delay in a language development results from the DENVER II test are related to children’s psychosocial functioning (p <0.05). Conclusion: Adequacy of nutrition and history of exclusive breastfeeding contribute to the size of the nutritional status of child growth if nutritional insufficiency continues and it is not handled with carefully there will be nutritional deficiencies during growth that will affect they development.